2017
DOI: 10.1158/1078-0432.ccr-16-2641
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA Methylation Profiling Reveals Methylation Markers Associated with 3q Gain for Detection of Cervical Precancer and Cancer

Abstract: Epigenetic host cell changes involved in cervical cancer development following a persistent high-risk human papillomavirus (hrHPV) infection, provide promising markers for the management of hrHPV-positive women. In particular, markers based on DNA methylation of tumor suppressor gene promoters are valuable. These markers ideally identify hrHPV-positive women with precancer (CIN2/3) in need of treatment. Here, we set out to identify biologically relevant methylation markers by genome-wide methylation analysis o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 52 publications
3
66
0
Order By: Relevance
“…These results correspond to the finding that only a subset of CIN2/3 will progress to cancer over a long time period [18,19]. Previous studies on copy number changes and DNA methylation levels of only a few genes also showed a cancer-like profile in only a subset of CIN2/3 lesions [11,14,20,21]. These lesions were characterized by a preceding hrHPV infection of >5 years and considered as more advanced lesions, which have a high short-term progression risk to cancer.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These results correspond to the finding that only a subset of CIN2/3 will progress to cancer over a long time period [18,19]. Previous studies on copy number changes and DNA methylation levels of only a few genes also showed a cancer-like profile in only a subset of CIN2/3 lesions [11,14,20,21]. These lesions were characterized by a preceding hrHPV infection of >5 years and considered as more advanced lesions, which have a high short-term progression risk to cancer.…”
Section: Discussionsupporting
confidence: 87%
“…Other unidentified underlying abnormalities may have resulted in increased DNA methylation levels. Considering a potential effect of age, i.e., 55 year for this control, DNA methylation levels of the markers tested were not or minimally affected by age in our previous studies using large cohorts [811,42,43]. Therefore, solely age is very unlikely to explain the cancer-like methylation-high pattern in this hrHPV-positive control.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…[9][10][11][12] Most of the earlier studies used a candidate gene approach focused on selected genes; other important genes may have been missed. In recent years, a number of powerful technologies have emerged that allow high-throughput detection of genome-wide epigenetic changes in diseases, [13][14][15] and especially, the bead array technology developed by Illumina could now provide genome-wide methylation status at single-nucleotide resolution. [16][17][18][19] However, these studies mainly were conducted in European or American populations; only a few samples from Asian populations were included.…”
Section: Introductionmentioning
confidence: 99%